2000
DOI: 10.1179/rer.2000.5.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Increased oxidative stress in rats with chronic nitric oxide depletion:measurement of urinary 8-hydroxy-2′-deoxyguanosine excretion

Abstract: Urinary 8-hydroxy-2'-deoxyguanosine (8-OHdG) has been reported to serve as a sensitive biomarker of oxidative stress. We examined the effect of chronic blockade of nitric oxide (NO) on urinary excretion of 8-OHdG in rats. Two types of NO synthase inhibitor were used: N(G)-nitro-L-arginine methyl ester (L-NAME) as a non-selective inhibitor and aminoguanidine (AG) as a selective inhibitor of the inducible isoform. Oral administration of L-NAME (20, 50 and 80 mg/dl of drinking water), but not AG (400 mg/dl), for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…In this context, previous experimental studies have also shown decreased levels of NOx in obese [34] as well as high-fatfed [35] rats. These findings are consistent with several reports that show the association between chronic NO deficiency induced hypertension and oxidative stress [36] . Plasma NOx levels were significantly increased on GOH supplementation, which may be due to the ability of GOH to induce eNOS.…”
Section: Discussionsupporting
confidence: 94%
“…In this context, previous experimental studies have also shown decreased levels of NOx in obese [34] as well as high-fatfed [35] rats. These findings are consistent with several reports that show the association between chronic NO deficiency induced hypertension and oxidative stress [36] . Plasma NOx levels were significantly increased on GOH supplementation, which may be due to the ability of GOH to induce eNOS.…”
Section: Discussionsupporting
confidence: 94%
“…2E) seen under NOS inhibition. Assuming that, under physiological conditions, NO serves to counteract increased oxidative stress produced by O 2 Ϫ (28,29) and NO fluxes exceed those of O 2 Ϫ under these conditions, then as the flux of NO drops due to NOS inhibition, it temporarily passes through the point where its value matches that of O 2 Ϫ , and thus to a level where production of ONOO Ϫ is optimal. This conjecture would account not only for the transient increases in NO-derived products but also for the appar- ent correlation between the amplitude of the nitrate͞nitrite ratios shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Maximum oxidant production will occur presumably by formation of ONOO -when fluxes of each radical are identical (the flux ratio of each radical is 1.0), especially in regions of low SOD activity. Endothelial activation (as represented by overproduction of O 2 -induced by TNF-α treatment [155][156][157][158]) and dysfunction (as represented by diminished NO synthesis [159][160][161]) might both produce a situation in which a situation of balance of NO and O 2 -in favor of NO is altered in favor of a more oxidative environment.…”
Section: Imbalance Of No/o 2 -Formationmentioning
confidence: 99%